Understanding your diabetes - Wise, Peter H. (London : Foulsham, 1999)
Contents.--v.1 For people with insulin-dependent (Type 1) diabetes.--v.2 For people with non-insulin dependent (Type 2) diabetes.
Keywords: Diabetes